Influence of timing and intensity of weed management on crop yield and contribution to weed emergence in cotton the following year. Issue 1 (11th April 2020) - Hare, Andrew T.; Jordan, David L.; Leon, Ramon G.; Edmisten, Keith L.; Post, Angela R.; Cahoon, Charles W.; Everman, Wesley J.; Mahoney, Denis J.; Inman, Matthew D.
Abstract: Adequate weed control is important in protecting crop yield and allowing efficient harvest in North Carolina. Data in the literature are limited with respect to direct comparisons of weed control and yield across multiple crops. Research is also limited in terms of documenting the impact of weed control in one crop on weed populations in the crop planted the following season. Experiments were conducted in North Carolina to determine weed control and yield of corn ( Zea mays L.), cotton ( Gossypium hirsutum L.), and soybean [ Glycine max (L.) Merr.] in the same experiment when herbicides were applied postemergence at different timings (Year 1) and to determine how weed control translated into weed populations and cotton yield the following year (Year 2). Herbicides were applied 2 or 6 wk after planting (WAP); 2 and 4 WAP; 4 and 6 WAP; and 2, 4, and 6 WAP. At Lewiston‐Woodville, common ragweed ( Ambrosia artemisiifolia L.) and Texas millet ( Urochloa texana L.) were present. At Rocky Mount, Palmer amaranth ( Amanthus palmeri S. Wats) and large crabgrass ( Digitaria sanguinalis L.) were present. A single postemergence application of herbicide protected yield from weed interference in corn, whereas in most instances multiple herbicide applications were needed in cotton and to a degree in soybean. Weed densities in Year 2 in cotton were negatively correlated with weed control the previous year in corn, cotton, and soybean. Densities of common ragweed and Palmer amaranth 3 WAP in Year 2 were higher in cotton when the preceding crop was cotton or soybean rather than corn when herbicides were not applied; no difference was noted when comparing cotton and soybean. In some instances, sequential applications of herbicides resulted in lower weed densities the following year in cotton. These results demonstrate the importance of timely, sequential herbicide applications for weed control in cotton and soybean and in some instances the positive benefits on weed populations the following year in cotton.